2021
DOI: 10.1039/d1cc02165f
|View full text |Cite
|
Sign up to set email alerts
|

Cost-efficient and user-friendly 17O/18O labeling procedures of fatty acids using mechanochemistry

Abstract: Two mechanochemical procedures for 17O/18O-isotope labeling of fatty acids are reported: a carboxylic acid activation/hydrolysis approach and a saponification approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…91 Here, enriched water was actually used to play the role of both a liquid grinding assistant and a reagent to introduce the isotopic label, in line with our previous work on isotopic labeling using ball-milling. [61][62][63][64][65][66] Three different experimental conditions were compared for the deuteration of COM. The first experiment adopted a very gentle approach: shaking without a milling ball, allowing the reagents to be mixed at the frequency of 25 Hz for 5 minutes (COM-SHAKE-2 H), and without any risk of affecting the crystallinity of the COM starting material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…91 Here, enriched water was actually used to play the role of both a liquid grinding assistant and a reagent to introduce the isotopic label, in line with our previous work on isotopic labeling using ball-milling. [61][62][63][64][65][66] Three different experimental conditions were compared for the deuteration of COM. The first experiment adopted a very gentle approach: shaking without a milling ball, allowing the reagents to be mixed at the frequency of 25 Hz for 5 minutes (COM-SHAKE-2 H), and without any risk of affecting the crystallinity of the COM starting material.…”
Section: Resultsmentioning
confidence: 99%
“…Building upon our recent demonstration that mechanochemistry can be a very powerful technique for enriching in 17 O various inorganic materials [61][62][63][64] and organic molecules. 63,65,66 Here, we will demonstrate for the first time that ball-milling methods are also very well suited for the 17 O-labeling or deuteration of hydrated biomimetic minerals like hydrated calcium oxalates.…”
Section: Introductionmentioning
confidence: 95%
“…81 Here, enriched water was actually used to play the role of both a liquid grinding assistant and a reagent to introduce the isotopic label, in line with our previous work on isotopic labeling using ball-milling. [54][55][56][57][58][59] Three different experimental conditions were compared for the deuteration of COM. The first experiment adopted a very gentle approach: shaking without a milling ball, allowing the reagents to be mixed at the frequency of 25 Hz for 5 minutes (COM-SHAKE-2 H), and without any risk of affecting the crystallinity of the COM starting material.…”
Section: Resultsmentioning
confidence: 99%
“…Building upon our recent demonstration that mechanochemistry can be a very powerful technique for enriching in 17 O various inorganic materials [54][55][56][57] and organic molecules. 56,58,59 Here, we will demonstrate for the first time that ball-milling methods are also very well suited for the 17 O-labeling or deuteration of hydrated biomimetic minerals like hydrated calcium oxalates.…”
Section: Introductionmentioning
confidence: 95%
“…Finally, in order to demonstrate the utility of sound measurements for the optimization of ball-milling reaction conditions, we decided to study the hydrolysis of an activated fatty acid, lauric acid, using this operando method. Indeed, during our previous work on the 17 O/ 18 O isotopic enrichment of fatty acids, 31,32 we had found that for saturated fatty acids, the hydrolysis time of the activated acyl-imidazole intermediates had to be systematically optimized by repeating the experiments with various milling times. Given that this hydrolysis is accompanied by a change in texture of the reaction medium, which switches from a powdery aspect to a more oily one, we suspected that acoustic measurements could be used to determine the time aer which the hydrolysis is complete (Fig.…”
mentioning
confidence: 99%